Investigation of the respiration rate during storage of fruit vegetables under the influence of abiotic factors - Priss, O.; Yevlash, V.; Zhukova, V.; Kiurchev, S.; Verkholantseva, V.; Kalugina, I.; Kolesnichenko, S.; Salavelis, A.; Zolovska, O.; Bandurenko, H. (My University, 2017)
The aim of the work was to establish the influence of most important abiotic planting factors (temperature, precipitation quantity) on the respiratory rate of fruit vegetables at storage and also a possibility of correction of respiratory metabolism by post-harvest thermal processing by antioxidant compositions. Fruits of cucumbers of the hybrids Masha and Afina, bush pumpkins Kavili and Tamino, sweet pepper of the hybrids Nikita and Hercules, tomato of the varieties Novachok and Rio Grande Original were used for the studies. It was established, that the respiratory rate of pumpkin fruit vegetables is importantly influenced by the variety specificity. The respiratory level of pumpkin vegetables directly correlates with the sum of active temperatures of the period of fruits formation and reversibly – with precipitation and hydrothermal coefficient. The influence of the variety specificity for nightshade vegetables is leveled, and among meteorological planting conditions the important intense influence on the respiratory rate is realized by the sum of active temperatures of the period of fruits formation and ripening. Precipitation and hydrothermal coefficient have the important influence only on pepper fruits. It was established, that the use of post-harvest thermal processing by antioxidant compositions results in inhibition of respiratory processes in fruit vegetables at storage.
Keywords: respiratory rate; storage; fruit vegetables; post-harvest thermal processing by antioxidants; abiotic factors